2009
DOI: 10.1021/om8011213
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Palladium(II)/Copper(II)-Catalyzed Oxidation of Olefins under Chloride-Free Nonacidic Conditions

Abstract: A chloride-free Pd(OAc)2/Cu(OAc)2 system catalyzes the oxidation of organic substrates by molecular oxygen in nonacidic methanol solutions. Terminal olefins, i.e., 1-hexene, 1-octene, styrene, and 2-vinylnaphthalene, give the corresponding methyl ketones without a significant double-bond isomerization of long-chain substrates. The catalyst also promotes an unusual allylic oxidation of sterically encumbered trisubstituted internal double bonds in acyclic polyenes able to form η2−η2-chelates with palladium. Lina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…[12,14,28] Studying the reactivity of eugenol and safrole we observed that their acetic acid solutions with catalytic amounts of PdCl 2 , CuCl 2 , and LiCl readily consumed dioxygen; however, only small amounts of the corresponding methyl ketones were detected. Most of the reacted substrates were converted into high boiling products which were not detectable by GC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[12,14,28] Studying the reactivity of eugenol and safrole we observed that their acetic acid solutions with catalytic amounts of PdCl 2 , CuCl 2 , and LiCl readily consumed dioxygen; however, only small amounts of the corresponding methyl ketones were detected. Most of the reacted substrates were converted into high boiling products which were not detectable by GC.…”
Section: Resultsmentioning
confidence: 99%
“…[7] However, the Wacker process requires large amounts of chloride ions and acid to maintain a catalytic cycle; therefore, the system is highly corrosive and often causes the formation of chlorinated side products. Although systems with various alternative halide-free co-catalysts, such as CuA C H T U N G T R E N N U N G (OAc) 2 , heteropoly acids, nitrates, and benzoquinone, have been intensively studied in attempts to reduce the environmental impact of these processes, [8][9][10][11][12][13][14] the reoxidation of palladium(0) during the catalytic cycle under more friendly conditions remains a critical challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, synthetic work has become more challenging where greener concept of chemical synthesis are required to overcome problems such as long reaction times [5], expensive oxidants [6][7], toxic solvents [8][9] and the simplicity of the work up procedures.…”
Section: Introductionmentioning
confidence: 99%
“…[1] However, the Wacker process requires large amounts of CuCl 2 , chloride ions, and acid to maintain the catalytic cycle; therefore, the system is highly corrosive and often causes the formation of chlorinated side products. To overcome these problems, much effort has been devoted to the development of alternative halide-free co-catalysts, such as CuA C H T U N G T R E N N U N G (OAc) 2 , heteropoly acids, nitrates, and benzoquinone; [2][3][4][5][6][7][8] as well as, more recently, palladium catalysts modulated by special ligands. [8][9][10][11][12][13][14] In the latter systems, oxidatively robust (usually, nitrogen-containing) ligands are used to stabilize reduced palladium and promote its regeneration directly by molecular oxygen avoiding the use of corrosive additives.…”
Section: Introductionmentioning
confidence: 99%